Epidemiological and serological profiles of TORCH infection in pregnancy (Journal of Pathology of Nepal, 2015)
Background: Maternal infections caused by TORCH [Toxoplasma gondii, Rubella virus, Cytomegalovirus (CMV), Herpes simplex virus (HSV)] are the major causes of bad obstetric history. The aim of this study was to evaluate the prevalence of TORCH infections in pregnancyMaterials and Methods:The study included 109 pregnant women with unfavorable previous pregnancy. Serological evaluation for TORCH infections was carried out by IgM Enzyme Linked Immunosorbant Assay method.  Data was analyzed using SPSS 17.0 whenever necessary.Results: The IgM/ IgG sero-positivity to T. gondii, Rubella, CMV and HSV-2 was 26.6/9.2 %, 9.2/78.9%, 17.4/58.7%, and 4.6/35.8 % respectively. There was an increased percentage of CMV infection. There was increased number of recent Toxoplasma infection in comparison to other studies conducted.Conclusion: A previous history of pregnancy wastage and the serological reaction for TORCH infections during current pregnancy must be considered while managing BOH cases so as to reduce the adverse fetal outcome.Journal of Pathology of Nepal (2015) Vol. 5, 705-708